NiO hollow microspheres as efficient bifunctional electrocatalysts for Overall Water-Splitting. (22nd November 2018) - Mondal, Aniruddha; Paul, Anirban; Srivastava, Divesh N.; Panda, Asit B.
Abstract: Development of efficient, earth-abundant and low-cost electrocatalyst for effective water electrolysis is highly demanding for production of sustainable hydrogen energy. In this paper, we report the cost-effective synthetic protocol for porous NiO hollow spheres in large scale through a simple spray drying strategy, using aqueous nickel ammonium carbonate complex solution, followed by calcination. The synthesized NiO hollow spheres calcined at 300 °C (NiO-300) are porous, made of nanoparticles in size range of 10–16 nm with a size range of 2.5–4 μm and total surface area of 120 m 2 /g. The NiO-300 exhibited excellent bifunctional electrocatalytic water splitting characteristic, both OER, and HER, in basic solution. NiO-300 modified glassy carbon electrode showed superior water electrolysis kinetics and to achieve 10 mA cm −2 current density, it required 370 mV overpotential for OER and 424 mV overpotential for HER in 1 M KOH. It is also worked well with cost-effective plastic chip electrode. An assembled two-electrode system by pairing NiO modified plastic chip electrode as both anode and cathode in a 1.0 M KOH electrolyte for overall water splitting exhibit clear bubble formation at 1.6 V potential. Graphical abstract: Highlights: Synthesis of porous NiO hollow spheres by spray drying followed by calcination. Showed efficient bifunctional electrocatalytic behaviour for Overall Water-Splitting. Reaches 10 mA/cm −2 current density at a overpotential of 370 mV in 1 M KOH for OER. 424 mV overpotential in required to achieve 10 mA cm −2 current density 1 M KOH for HER. Exhibit clear bubble formation at 1.6 V potential in an assembled two-electrode system.